Adverse Drug Reactions in the Oral Cavity - Danko Velimir Vrdoljak; Vanja Vučićević Boras; Vlaho Brailo; Sonja Kraljević Šimunković; Dragana Gabrić; Ana Andabak-Rogulj (Acta Clinica Croatica, 2015)
Every medication may lead to adverse effects, even when used in standard doses and mode of application. In the oral cavity, adverse effects may affect every part of oral mucosa and are the result of medications taken either locally or systemically. Oral adverse reactions to drugs are not typical and therefore sometimes not easy to recognize. On diagnosing adverse side effects in the oral cavity, experienced clinician will usually diagnose the condition on the basis of detailed medical history and clinical finding. However, the only objective evidence for the offending drug is ‘re-challenge’, i.e. exposure to the drug after its discontinuation. It carries a huge risk of anaphylactic reaction; therefore it has to be performed in a controlled hospital setting. Therapy is based on immediate exclusion of the offending drug and, if lesions are present in the oral cavity, topical or systemic corticosteroid therapy is prescribed. This article gives a review of patients with oral adverse drug reactions referred to the Department of Oral Medicine in Zagreb.